2017
DOI: 10.1186/s12889-016-3952-6
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to hepatitis C virus in homeless men in Central Brazil: a cross-sectional study

Abstract: BackgroundHomeless men are highly vulnerable to acquisition of the hepatitis C virus (HCV) compared to the general population. In Brazil, a country of continental dimensions, the extent of HCV infection in this population remains unknown. The objective of this study is to investigate the epidemiological profile of exposure to HCV in homeless men in Central Brazil.MethodsA Cross-sectional study was conducted in 481 men aged over 18 years attending therapeutic communities specialized in the recovery and reintegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
1
10
1
2
Order By: Relevance
“…In the absence of an approved prophylactic vaccine for hepatitis C, reducing exposure to HCV through prevention seems to be the best option. This can be achieved through routine screening of donated blood for HCV markers, providing safe medical procedures, promoting risk-reduction counseling and services for at risk population, increasing public awareness and offering regular HCV testing to high-risk populations with the goal of breaking the cycle of HCV transmission in the society[ 7 , 9 , 82 , 133 ]. Despite the so-called improvements in the management of HCV infection, still a long way is ahead to achieve a world free of HCV infection.…”
Section: Progresses In the Management Of Hcv Infectionmentioning
confidence: 99%
“…In the absence of an approved prophylactic vaccine for hepatitis C, reducing exposure to HCV through prevention seems to be the best option. This can be achieved through routine screening of donated blood for HCV markers, providing safe medical procedures, promoting risk-reduction counseling and services for at risk population, increasing public awareness and offering regular HCV testing to high-risk populations with the goal of breaking the cycle of HCV transmission in the society[ 7 , 9 , 82 , 133 ]. Despite the so-called improvements in the management of HCV infection, still a long way is ahead to achieve a world free of HCV infection.…”
Section: Progresses In the Management Of Hcv Infectionmentioning
confidence: 99%
“…Multiple regression analysis, as well as the other studies, revealed an association between exposure to HBV and age increase [14, 20, 36, 40]. The displacement of the epidemiological curve of HBV in populations with higher age groups can be explained by the Brazilian policy of increasing the age for eligibility of hepatitis B vaccine over the years [34].…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, bivariate Poisson analysis was performed to verify the potential factors associated with HBV exposure. Variables that were included in the Poisson regression model were those with robust variance [14, 32, 33] with p -value < 0.20 in the bivariate analysis. The final modelling of factors associated with HBV infection was adjusted for age, sex, education, history of hepatitis in the family, injecting drug use, sexual intercourse under the influence of alcohol, the age at the time of sexual intercourse, STI history, and exposure to T. pallidum .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in Rio de Janeiro, Brazil, with 4,897 individuals tested for the presence of HCV, there were 1,180 HCV RNA-positive cases, and a significant association between RNA positivity and drug use but not with tattoos and piercings was found 23 . In the state of Goiás, Central Brazil, a study on 481 homeless men showed a significant association between HCV infection and drug use, number of sexual partners, and sexually transmissible diseases; however, there was no 7/8 association between HCV infection and the presence of tattoos and piercings 24 . A study of drug users in the Island of Marajó, Amazon showed that age (35 years), presence of tattoos, IDU, sharing injection equipment, and daily and prolonged use (>3 years) of illegal drugs were associated with HCV positivity 25 .…”
Section: Discussionmentioning
confidence: 98%